2011
DOI: 10.1021/jp201946a
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Multiple Photon Dissociation Action Spectroscopy and Computational Studies of Mass-Selected Gas-Phase Fluorescein and 2′,7′-Dichlorofluorescein Ions

Abstract: Fluorescein (FL) and its derivative 2',7'-dichlorofluoroescein (DCF) are well-known fluorescent dyes used in many biological and biochemical applications. Although extensive studies have been carried out to investigate their chemical and photophysical properties in different solvent media, little is known about their intrinsic behaviors in the gas phase. Here, infrared multiple photon dissociation (IRMPD) action spectra are reported for the three charged prototropic forms of FL and DCF and compared with comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 67 publications
5
36
0
Order By: Relevance
“…Interestingly, very similar fragmentation pattern was reported for both [FL + H] + and [FL − H] − in IRMPD experiments 20 . This points, for both excitation schemes (nanosecond IRMPD and femtosecond UV/Vis), toward dissociation starting from highly vibrationally excited electronic ground states.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, very similar fragmentation pattern was reported for both [FL + H] + and [FL − H] − in IRMPD experiments 20 . This points, for both excitation schemes (nanosecond IRMPD and femtosecond UV/Vis), toward dissociation starting from highly vibrationally excited electronic ground states.…”
Section: Resultssupporting
confidence: 79%
“…This fragmentation pattern was noted before in Refs. 18 and 19 and also observed in IR multiple-photon dissociation (IRMPD) experiments 20 . Furthermore, [FL + H] + exhibits a much lower fragmentation yield than [FL − H] − , even when applying higher pump photon energy and intensity for photoexcitation (425 nm vs. 520 nm excitation wavelength and an intensity of 0.8  μ J vs. 0.3  μ J, respectively).…”
Section: Resultsmentioning
confidence: 75%
“…The recent studies of the structure and spectra in the gas phase are of special interest [10][11][12][13][14]. The evident reason of such activities is the expanding applications of the abovementioned compounds in versatile fields, including biochemistry [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the neutral form exists in solution as a mixture of three tautomers, zwitterion H 2 Z ± , quinonoid H 2 Q, and colorless lactone H 2 L, only the carboxylate tautomer, HQ À , is typical for the monoanion. The phenolate tautomer HX À appears in small quantities only in pure non-hydrogen bond donor solvents, such as DMSO, acetonitrile, and acetone [29], but it predominates in the gas phase [10][11][12][13][14]. For the derivatives bearing halogen atoms in the xanthene moiety, such as eosin, the zwitterionic tautomer is less typical, whereas the monoanion exists predominantly as HX À [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy, and in the gas-phase by IRMPD. [41][42][43] Narayaman et al found that the FTIR of EY in solution contains many intense absorption features between 1000 and 2000 cm -1 . Yao et al measured gas-phase fluorescein and 2',7'-dichlorofluorescein by IRMPD action spectroscopy and found a similar series of intense vibrational transitions in the same energy range.…”
Section: Resultsmentioning
confidence: 99%